Leasing in Europe and the review of international lease accounting - Jaqueline Mills (Leasing - Wissenschaft & Praxis, 2008)
The text is intended to give a flavour of a speech given by Jacqueline Mills, Senior Adviser Leaseurope, during the annual meeting of the German Leasing Research Institute. She reported that the European leasing market was the largest market in the world in 2007. Lessors in Europe granted new leasing volumes of just under 340 billion EUR (+12.4%). The overall growth for the first half of the year 2008 compared to 2007 is just over 1%. Standard setters make several arguments to justify why current lease accounting, the economic ownership model, has to be changed. The model of economic ownership leads to the recognition of assets and liabilities on lessee's balance-sheet that is not consistent with the definitions of assets and liabilities by IASB. Other issues are classification issues concerning the decision of whether or not a lease is a finance or an operating lease. The IASB and FASB have decided that lessee accounting should be completed by June 2011, but there are some issues that still need to be clarified. Leaseurope has been working on developing the concept of an exemption of leases of non-core assets. For a better understanding of the impact on lessee's financial accounting, the speaker presents a numerical example.
Keywords: 330; Leasinggesellschaft; International Financial Reporting Standards; EU-Staaten